Adsorption kinetics and isotherm models of heavy metals by various adsorbents: An overview - Wang, Jianlong; Guo, Xuan (Critical reviews in environmental science and technology, 2023)
Heavy metal pollution has become one of the most severe environmental issues. Adsorption is an effective method for removing heavy metals from aquatic environments. The adsorption isotherm and kinetics models can provide information on the adsorption process, maximal adsorption capacity, and mass transfer steps, which are essential to evaluate the performance of an adsorbent and to design an adsorption system. In this review, the adsorption kinetics and isotherms of heavy metals by various adsorbents were summarized and discussed in depth. First, the sources of heavy metal pollution and the adsorption technology to remove heavy metals were reviewed. The adsorption capacity of Cu, Cd, Zn, Ni, Cr, As, Fe, Hg, Co, Sr, and Cs by biosorbents (e.g. algae, agriculture waste biochar/activated carbon, and bacteria) and by abiotic adsorbents (e.g. metal-organic frameworks (MOFs), microtubes, polymers, clays, minerals, and coal) were systematically summarized. Second, the origins, basic assumptions, importance, physical meanings, and applications of the adsorption kinetics and isotherm models were discussed in depth. Third, the methods for selecting adsorption models in different conditions were explained, and the statistical parameters which can be applied to evaluate the performance of the models were illustrated. Finally, two Excel sheets are provided for solving the adsorption models, which are available in Supplementary Information . This review article will deepen the understanding of the interaction between heavy metals and adsorbents and facilitate the development of adsorptive technology for heavy metal removal from water and wastewater.